Blockchain as a Notarization System for Military Data Sharing - Chatchawan Chamnikul; Amnach Khawne (My University, 2025)
This paper presents a blockchain-based notarization system designed to secure and authenticate military data sharing. In the context of national defense, where the integrity and confidentiality of sensitive military data are paramount, traditional centralized systems often fail to meet the required security standards. Our proposed system leverages a permissioned blockchain platform, specifically Hyperledger Fabric, combined with smart contracts to create an immutable and transparent ledger. This ensures that once military data is recorded, it cannot be altered or tampered with, thereby enhancing data integrity and auditability. The system is further integrated with existing military information infrastructures through secure APIs and middleware, enabling seamless data exchange. Experimental evaluations conducted in a simulated environment demonstrate that the system achieves high transaction throughput, low latency, and robust error management. Although challenges remain in scalability and fine-grained access control, the results confirm that blockchain technology has the potential to significantly improve the security and transparency of military data sharing. Future work will focus on addressing these challenges and refining the system for real-world deployment in defense operations.
Keywords: Cloud Data Security Solutions